Parents' Motivation for Their Child's First Visit to The Dentist (A Descriptive Study) - Setiawan, Irfan Maulana Aji; Sari, Nendika Dyah Ayu Murika; Kaswindiarti, Septriyani; Kurniawati, Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Introduction: Dental health in children plays a crucial role in their growth and development. According to the RISKESDAS results in 2018, 54% of children aged 5-9 years experience dental and oral health problems. Parents play a vital role in the oral health care of children and initiate visits to the dentist. Factors influencing parents to take their children to the dentist include motivation. This research aims to provide an overview of parents’ motivation during their child's first visit to the dentist. Methods: This study involved 126 parents with children aged 7-9 years, with ethical approval from Dr. Moewardi Hospital Number 1.981/XI/HREC/2023. Inclusion criteria were parents of Nur Hidayah Elementary School students with children aged 7-9 years, having experience taking their children to the dentist, living with the child, and being willing to participate. Data collection was conducted in October-November 2023, using a Google Form consisting of 11 questions. Results: The research results indicate that the highest percentage of children's dental visits is at the age of >5 - ≤ 7 years, accounting for 37% . The percentage of parental motivation during the child's first visit to the dentist is divided into 57% internal motivation and 43% external motivation. The primary motivation for the visit is dental complaints, accounting for 61.9% , including tooth extraction (37%), restoration (12%), toothache (8%), orthodontic (2%), caries (2%), calculus (1%), and trauma (1%). The results also show that 33% come for routine check-ups, 2% for preventive care, and 2% to introduce the dental profession. Conclusion: Parents have higher external motivation than internal motivation during their child's first visit to the dentist. The most common reason for parents to take their child to the dentist is dental complaints, with the most common complaint is tooth extraction.